Systems biology approaches to investigating the roles of extracellular vesicles in human diseases - András Gézsi; Árpád Kovács; Tamás Visnovitz; Edit I. Buzás (Experimental and Molecular Medicine, 2019)
Diagnostics: A closer look at extracellular vesicles Cells routinely release tiny membrane vesicles whose contents can potentially be used as indicators for various diseases. Long viewed as a system for garbage removal, researchers now recognize that these extracellular vesicles transport proteins, nucleic acids and metabolites that play an important role in cell signaling and other functions. Edit Buzás and colleagues at Semmelweis University in Hungary have reviewed the various databases that researchers have used to classify and characterize the various molecules contained within these vesicles. A number of studies indicate that the contents of vesicles might prove informative in diagnostic assays for various diseases. The authors also employed a strategy for integrating multiple extracellular vesicle datasets in order to identify genes, proteins and cell signaling pathways that represent possible connections between these vesicles and different medical conditions.